THE INTERPRETATION OF “FIRE” IN INDONESIAN AND ENGLISH PROVERBS: A COGNITIVE SEMANTICS ANALYSIS - Nur Lailatul Aqromi (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
It is believed that proverbs from each nation reflect the nation’s thoughts and characters. Based on the relationship between human conceptualization and language reflected in proverbs, then this study attempts to examine Indonesian proverb and English proverb by using a cognitive semantics approach. The data are taken from Indonesian proverb and English proverb containing api or “fire” word as it is one of the natural symbols of human life. Furthermore, based on the comparison of 7 Indonesian proverbs and 8 English proverbs containing api or “fire” word, the results of the study show that there are two categories created: first, proverbs in the same form and meaning including the risk mapping, anger and work; second, proverbs from the same form but different meanings.